The Battlefield of IoT: Competitive and Cooperative Relationship Among Smart Home Vendors - Kuang-Chiu Huang; Yu-Cheng Lin (International Telecommunications Society (ITS), 2017)
The integration between electronic devices and networking enable convenient, comfortable, efficient and secure life. So there are a variety of smart home hubs and accessories migrating to daily life with all kinds of possibilities and extending the scope and coverage of Internet of Things (IoT). For an example, Amazon's Echo launched in June 2015 and offers amazing capabilities. Its artificial intelligence voice assistant Alexa is a breakthrough invention, and people can not only search information, play music, read daily news, and place order instantly but also control auxiliary devices as television, air conditions, curtains, lights by their voice. In addition, the membership of Amazon, a giant of e-commerce, has reached to 65 millions prime membership and promotes Echo with affordable price 179 and five millions sales record. To exploit the value of network of this emerging market, Amazon has welcomed and invited third-party vendors to develop unique voice skills together and to establish the ecosystem effectively. Although Google's Home launched lately in October 2016, its artificial intelligence voice assistant -Google Assistant is embedded strengths of Google search engine and sells for a competitive price 139 only. Google adopts the similar strategy to expand the eco-systems of smart home actively enhance smart home network effect with their huge resources. On the contrary, smart home hub vendors, Amazon, Google, and Samsung, not only compete each other, but also cooperate to enlarge this booming market together. For examples of cooperation case, the products of Nest which owned by Google compatible with Amazon's Echo. Relatively, smart home auxiliary vendors, Philips, Nest, and Smartthings, adopt several strategic alliance with smart home hub vendors to compete on the one side and cooperate on the other side. Therefore, the interaction between hub vendors and auxiliary device vendors is an amazing game and affects the development of IoT future. Our study will outline its competition status and answer the question “how do stakeholders of smart home market cooperate and compete each other in the emerging stage?” The research method adopts three steps analysis for thorough study of the question. The Resource-based model from industry organization to analyze those smart home hub vendors for the 1st step. Value net model, Porter's diamond model, and Ansoff matrix are analysis methods to be applied in the 2nd step for discussing external environment. And then, we enrich interaction discussion through case study as the last step. In the resource-based model, we address internal resources, capabilities, and core competences for both hub vendors and auxiliary device vendors to analyze competitive advantages. External analysis uses value net model to figure out how to develop strategies of horizontal and vertical competition in smart home industry. Also, we evaluate the capabilities of potential revenues and profits to analyze the relationship of each smart home hub enterprises, customers, suppliers, competitors, and complementors (smart home auxiliary vendors). Porter's diamond model mainly focuses on market demand and government policies whether affect enterprises decisions, and chooses Ansoff matrix to analyze the development of different smart home products in different markets development decisions. Based on the prior analysis results, then we can take overall analysis on market level about the co-opetition relationship of network effect on smart home.
Keywords: 330; IoT; smart home; value net model; Porter's diamond model; case study; Ansoff matrix; co-opetition